2013
DOI: 10.1007/s12070-013-0679-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Correlates of Behavioral Comfort Levels in Cochlear Implantees: A Prospective Study

Abstract: Indications for cochlear implantation have expanded today to include very young children and those with syndromes/multiple handicaps. Programming the implant based on behavioral responses may be tedious for audiologists in such cases, wherein matching an effective MAP and appropriate MAP becomes the key issue in the habilitation program. In 'Difficult to MAP' scenarios, objective measures become paramount to predict optimal current levels to be set in the MAP. We aimed, (a) to study the trends in multi-modal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
8

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 12 publications
(39 reference statements)
0
12
0
8
Order By: Relevance
“…Clinical studies in human CI users have been also conducted on electrophysiological and behavior measurements. The electrically evoked compound action potential (ECAP) has been widely used as a valuable objective tool in mapping the CI, especially for those who have difficulty in showing the reliable behavioral response [12]. Whereas some studies reported that the ECAP threshold, T level, and C level were lower for the PM than the LW, and were lower on the apical region than on the basal and medial regions [13-15], other studies showed different results [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies in human CI users have been also conducted on electrophysiological and behavior measurements. The electrically evoked compound action potential (ECAP) has been widely used as a valuable objective tool in mapping the CI, especially for those who have difficulty in showing the reliable behavioral response [12]. Whereas some studies reported that the ECAP threshold, T level, and C level were lower for the PM than the LW, and were lower on the apical region than on the basal and medial regions [13-15], other studies showed different results [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Uno de los problemas principales en la realización del ePEATC en pacientes pediátricos es la cooperación ya que este examen requiere de más tiempo 11 . Aun con estas limitaciones, el ePEATC puede ser de gran utilidad en casos de mapas erróneos que han sido pasados por alto con mediciones de ECAP o del eREE 6 , en casos de disfunción/ disincronía de la vía auditiva 11,20 , o en casos en los cuales no fue posible detectar un ECAP 19 . Es decir, casos para los cuales la programación puede ser más dificultosa.…”
Section: Discussionunclassified
“…Para los pacientes pediátricos de menor edad (i.e. lenguaje limitado, experiencia inadecuada con el sonido y no pueden dar respuestas conductuales confiables), y los pacientes con dificultades para proporcionar una retroalimentación adecuada, la programación del implante puede ser más dificultosa 6 . Una buena programación del implante es crucial y se realiza de forma individualizada, esto permite que el paciente implantado pueda: -Detectar y discriminar los sonidos de la voz humana en relación al lenguaje oral, -lograr niveles de audición óptimos, -evitar experiencias desagradables que propicien el rechazo del implante, y -evitar una percepción acústica alterada que impacte el desarrollo del lenguaje oral 7 .…”
Section: Introductionunclassified
“…With origins of waves similar to those in ABR, EABR can theoretically reflect the functional state of the auditory pathway in the acoustic nerve of the brainstem, and it has a high extraction rate. Furthermore, as the objective indicator of audiometry, the EABR threshold can be used to assess the efficacy of implantation [20][21][22][23]. The cerebral cortex is involved in testing the subjective threshold (T-level values).…”
Section: Discussionmentioning
confidence: 99%